Exploitation and community engagement: Can Community Advisory Boards successfully assume a role minimising exploitation in international research?. Issue 1 (31st May 2013) - Pratt, Bridget; Lwin, Khin Maung; Zion, Deborah; Nosten, Francois; Loff, Bebe; Cheah, Phaik Yeong
Abstract It has been suggested that community advisory boards (CABs) can play a role in minimising exploitation in international research. To get a better idea of what this requires and whether it might be achievable, the paper first describes core elements that we suggest must be in place for a CAB to reduce the potential for exploitation. The paper then examines a CAB established by the Shoklo Malaria Research Unit under conditions common in resource‐poor settings – namely, where individuals join with a very limited understanding of disease and medical research and where an existing organisational structure is not relied upon to serve as the CAB. Using the Tak Province Border Community Ethics Advisory Board (T‐CAB) as a case study, we assess the extent to which it might be able to take on a role minimising exploitation were it to decide to do so. We investigate whether, after two years in operation, T‐CAB is capable of assessing clinical trials for exploitative features and addressing those found to have them. The findings show that, although T‐CAB members have gained knowledge and developed capacities that are foundational for one‐day taking on a role to reduce exploitation, their ability to critically evaluate studies for the presence of exploitative elements has not yet been strongly demonstrated. In light of this example, we argue that CABs may not be able to perform such a role for a number of years after initial formation, making it an unsuitable responsibility for many short‐term CABs.